ECOLOGY OF EARTH: CONDITION, PROSPECTS OF TRANSFORMATION AND PROPHYLACTIC MEASURES ON PLANETARY SCALE - T. A. Shebzukhova; M. F. Marshalkin (Современная наука и инновации, 2022)
The factors, causing the negative influence upon the environment, the causes, generating these factors and their transformation on a scale of the planet are depicted in this article and the new vital formula for saving life on the earth is proposed as well.